MANAJEMEN PENGEMBANGAN DIRI DALAM PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DI STITNU AL-FARABI PANGANDARA - Irpan Ilmi; Isyfi Agni Nukhbatillah (Institut Madani Nusantara, 2023)
Students are often referred to as agents of change or carriers of change agents and movers for the surrounding environment towards a better direction. Through their knowledge, ideas and skills, students can become locomotives of progress. This is inversely proportional to the existing reality. Many of today's generation of students have low levels of self-confidence. The main reason is not recognizing one's own strengths and worth in the midst of society. In addition, almost all students only see external causes that are material. This becomes serious, because it can be a long chain of unemployment for undergraduate graduates. Departing from this, Community Service with the material title